Kinect based human body measurement V2 - Hady Januar Willi (2015)
The development of fast Kinect based human body measurement has paved a way for this method to be used by commercial sites and entertainment industry. Human body measurements are important data for online shopping web sites, and virtual and augmented reality entertainment. This project proposes improvements for Fast Human Body Measurement Based on A Single Kinect [1], which has provided a fast and good quality human body measurement method using a single Kinect. The improvements proposed are based on user interface, and increase the use case of the software by implementing server-client solution. The results of the project shows that the new implementation are beneficial to the previous project.